Winning during a pandemic: epidemiology of SARS-CoV-2 during EURO2020 in Italy. (22nd April 2022) - Riccardo, Flavia; Frisicale, Emanuela Maria; Guzzetta, Giorgio; Ferraro, Federica; Merler, Stefano; Maringhini, Guido; Spuri, Matteo; Petrone, Daniele; Rota, Maria Cristina; Rapiti, Alessia; Angeloni, Ulrico; Rossi, Pasqualino; et al.
Abstract: Introduction: EURO2020 generated a growing media and population interest across the month period, that peaked with large spontaneous celebrations across the country upon winning the tournament. Methods: We retrospectively analysed data from the national surveillance system (indicator-based) and from event-based surveillance to assess how the epidemiology of severe acute respiratory syndrome coronavirus 2 (SARS CoV-2) changed in June–July 2021 and to describe cases and clusters linked with EURO2020. Results: Widespread increases in transmission and case numbers, mainly among younger males, were documented in Italy, none were linked with stadium attendance. Vaccination coverage against SARS-CoV-2 was longer among cases linked to EURO2020 than among the general population. Conclusions: Transmission increased across the country, mainly due to gatherings outside the stadium, where, conversely, strict infection control measures were enforced. These informal 'side' gatherings were dispersed across the entire country and difficult to control. Targeted communication and control strategies to limit the impact of informal gatherings occurring outside official sites of mass gathering events should be further developed.